Analysis of integrated marketing communication in strengthening brand image: comparative study of Ayam Bang Dava and Mang Katsu Brand under PT. Senang Ganyang Lapar - Nurrohmah, Syifa; Chan, Arianis; Muttaqin, Zaenal (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study examines two virtual restaurant brands—Ayam Bang Dava and Mang Katsu—as the research objects. This research offers a novel comparative analysis of Integrated Marketing Communication (IMC) strategies implemented by two brands operating under the same parent company within a shared cloud kitchen environment—a context that remains underexplored in existing academic literature. It aims to compare how each brand’s IMC strategies influence brand image across five dimensions (public relations, promotion, events, digital interaction, packaging). Employing a sequential exploratory mixed-methods design, qualitative data were gathered via interviews and observations, then quantitative data were collected through consumer questionnaires (purposive and accidental sampling). Qualitative findings were analyzed with the Miles and Huberman model; quantitative differences were tested using the Mann-Whitney U test. Results indicate significant inter-brand differences in promotional messages and media use (p < 0.05), digital personalization and dialogue quality (p < 0.05), and use of packaging for promotion (p < 0.05). In terms of brand image, credibility and visual recognition differed significantly (p < 0.05), as did personal, experiential, and economic benefits (p < 0.05). Practically, this study contributes to a deeper understanding of how differentiated IMC approaches within a unified operational structure can support brand development—particularly for emerging brands like Mang Katsu—while maintaining competitive parity in overall communication effectiveness (p = 0.774).